Mutation-driven evolution of antibacterial function in an ancestral antifungal scaffold: Significance for peptide engineering - Gu, Jing; Isozumi, Noriyoshi; Gao, Bin; Ohki, Shinya; Zhu, Shunyi (Frontiers in Microbiology, 2022)
Mutation-driven evolution of novel function on an old gene has been documented in many development- and adaptive immunity-related genes but poorly understood in immune effector molecules. Drosomycin-type antifungal peptides (DTAFPs) are a family of defensin-type effectors found in plants and ecdysozoans. Their primitive function was to control fungal infection and was then co-opted for fighting against bacterial infection in plants, insects and nematodes. This provides a model to study the structural and evolutionary mechanisms behind such functional shift. In the present study, we determined the solution structure of mehamycin, a DTAFP from the Northern root-knot nematode Meloidogyne hapla with antibacterial activity and an 18-mer insert, and functionally compared its wild-type peptide with a mutant with the insert deleted to study the mutational effect. Mehamycin adopts an expected cysteine-stabilized α-helical and β-sheet fold in its core scaffold and the inserted region, called single Disulfide Bridge-linked Domain (abbreviated as sDBD), forms an extended loop protruding from the scaffold. The latter folds into an amphipathic architecture stabilized by one disulfide bridge, which likely confers mehamycin a strong bacterial membrane-disruptive ability. Deletion of the sDBD remarkably decreased the ability but accompanying an increase in thermostability, indicative of a structure-function trade-off in the mehamycin evolution. Allosteric analysis revealed an interior interaction between the two domains, which might promote point mutations at two key sites of the core domain and ultimately give rise to the emergence of antibacterial function. Our work may be valuable in guiding protein engineering of mehamycin to improve its activity and stability.